Impact of universal varicella vaccination on 1-year-olds in Uruguay: 1997–2005. Issue 10 (2nd May 2008) - Quian, J; Rüttimann, R; Romero, C; Dall'Orso, P; Cerisola, A; Breuer, T; Greenberg, M; Verstraeten, T
Abstract : Objective: Varicella vaccination was introduced at the end of 1999 into the Uruguayan immunisation schedule for children aged 12 months. Varilrix (Oka strain; GlaxoSmithKline Biologicals) has been the only vaccine used since then and coverage has been estimated to exceed 90% since the start of the universal varicella vaccination programme. We assessed the impact of the Uruguayan varicella vaccination programme during 2005, 6 years after its introduction. Methods: Information on hospitalisations was collected from the main paediatric referral hospital and information on medical consultations for varicella was collected from two private health insurance systems in Montevideo. The proportion of hospitalisations due to varicella and the proportion of ambulatory visits for varicella since the introduction of the vaccine were compared between 1999 and 2005 and 1997 and 1999 in the following age groups: <1 year, 1–4 years, 5–9 years and 10–14 years. Results: By 2005, the proportion of hospitalisations due to varicella among children, was reduced by 81% overall and by 63%, 94%, 73% and 62% in the <1, 1–4, 5–9 and 10–14 years age groups, respectively. The incidence of ambulatory visits for varicella among children was reduced by 87% overall and by 80%, 97%, 81% and 65% in the <1, 1–4, 5–9 and 10–14 years age groups, respectively. Conclusions: The burden of varicella has decreased substantially in Uruguayan children since the introduction of the varicella vaccination, including those groups outside the recommended vaccination age. It is expected to decrease further as more cohorts of children are vaccinated and herd immunity increases.